Slogan Merokok Mati,Tidak Merokok Mati, Mending Merokok Sampai Mati : Kajian Filosofis-Sufistik - Muntaha, Darul; El Syam, Robingun Suyud (STAI Denpasar Bali, 2023)
This article aims to answer big questions about the slogan smoking to death, don't smoke to death, it's better to smoke until you die: a philosophical-sufistic study. This paper uses a literature approach with a philosophical-sufistic conception, and is analyzed inductively. The results of the study show that the destiny of death is God's prerogative, no one can avoid it when the time comes. The mystery of death and Islamic eschatology in a Sufistic framework in order to achieve self-perfection in living the teachings of Islam, so when you can avoid smoking in order to live the teachings of Islam, then that is good, on the other hand, enjoying cigarettes as a way to get closer to Allah is not bad. However, it needs to be underlined that the belief that death is God's right needs to be put forward, while the dangers of smoking are only a medium, nothing more than that. Research implications: the importance of a philosophical-sufistic perspective for assessing an action in depth. The research contributes to the philosophical-sufistic meaning of slogans for the direction of multidisciplinary research in the future.